Effective Physical Security - Fennelly, Lawrence (Butterworth-Heinemann, 2016)
Effective Physical Security, Fifth Edition is a best-practices compendium that details the essential elements and latest developments in physical security protection. This new edition is completely updated, with new chapters carefully selected from the author's work that set the standard. This book contains important coverage of environmental design, security surveys, locks, lighting, and CCTV, the latest ISO standards for risk assessment and risk management, physical security planning, network systems infrastructure, and environmental design.